2015
DOI: 10.1111/aeq.12103
|View full text |Cite
|
Sign up to set email alerts
|

“She Don't Know I Got It. You Ain't Gonna Tell Her, Are You?” Popular Culture as Resistance in American Preschools

Abstract: Popular culture is often a site of contestation in preschool classrooms. A multisited ethnographic design revealed preschools employed varied strategies to limit popular culture. Teacher and children's actions were considered through Michel de Certeau's (1984) concepts of tactics and strategies. Interviews and observations revealed children were well aware of rules limiting popular culture and agentively engaged in tactical resistance in order to insert their voices into the preschool curriculum. [popular cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Many American teachers, parents, and other adults try to limit young children’s access to popular media in favor of adult-curated toys, stories, and games, which are more aligned with adult constructions of proper childhood (Jenkins, 1998). This is also a product of constructions of “good” adult identities wherein Barbies, Spiderman, and other figures of children’s media are “banal, superfluous, distasteful [and] plebian” (Henward, 2015: 208) and access to them a sign of supervisory adult shortcomings.…”
Section: Media As Ketmentioning
confidence: 99%
See 3 more Smart Citations
“…Many American teachers, parents, and other adults try to limit young children’s access to popular media in favor of adult-curated toys, stories, and games, which are more aligned with adult constructions of proper childhood (Jenkins, 1998). This is also a product of constructions of “good” adult identities wherein Barbies, Spiderman, and other figures of children’s media are “banal, superfluous, distasteful [and] plebian” (Henward, 2015: 208) and access to them a sign of supervisory adult shortcomings.…”
Section: Media As Ketmentioning
confidence: 99%
“…Henward (2015) looked specifically at teachers’ treatment of children’s popular media, including both boys’ and girls’ media. Henward found that teachers had dismal regard for children’s popular media and limited children’s access to that media accordingly.…”
Section: Media As Ketmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars working in popular culture studies (Storey, 2018), media studies (Buckingham, 2015; Jenkins and Ito, 2015), literacy studies (Alvermann, 2002; Dyson, 1997, 2015; Evans, 2011; Marsh, 1999; Moje et al, 2004; Simmons, 2014; Wohlwend, 2017; Yoon, 2018) informal learning (Henward, 2015b), and digital learning (Hatzigianni, 2018) consider the incorporation of popular cultural texts and themes as salient pedagogical approaches and worthy topics of curriculum in schools. Typically employing ethnographic and highly contextualized qualitative methods, these scholars embrace symbolic or interpretivist, critical, post-modern, and post-structural traditions to recognized the social and cultural world of children and commercial media as a profound influence on, and a connection to, the education practices of children.…”
Section: Introductionmentioning
confidence: 99%